HIV in the Caribbean : A Systematic Data Review, 2003-2008 - World Bank (Washington, DC, 2013)
This report is the result of a comprehensive, regional, data-driven review of the HIV epidemic in the Caribbean. Several reports have been published about the Caribbean but none have specifically focused on a thorough review of data sources, data collection strategies and detailed epidemiology of the HIV epidemic. In the past, the Caribbean epidemic has largely been characterized as a generalized, heterosexual epidemic on the verge of explosion. The purpose of an HIV epidemiological synthesis is to assess and analyze new or recent data to provide strategic direction for the program development and implementation. New data sources include any unpublished, unexplored or unanalyzed data, the latest surveillance data, as well as, biological and behavioral surveys, STI data, program monitoring data and quantitative or qualitative research data. The synthesis also tests and explores an existing hypothesis about the epidemic and discusses relevant data-based policy implications. For the Caribbean synthesis, aimed to: 1) analyze HIV transmission patterns; 2) determine epidemiological and behavioral drivers in the Caribbean; and 3) analyze the national and regional responses relative to findings from the analysis.